2017
DOI: 10.3892/ol.2017.6866
|View full text |Cite
|
Sign up to set email alerts
|

Role and underlying mechanisms of the interstitial protein periostin in the diagnosis and treatment of malignant tumors (Review)

Abstract: Abstract. Invasion and metastasis are the major characteristics of malignant tumors and are complex processes involving multiple genes. Gene regulation is a precise, large and complex biological control system, and its underlying mechanisms remain to be elucidated. Mesenchymal-specific genes are expressed primarily by mesenchymal cells, and the expression products of these genes are molecules with various structures and functions, including secreted proteins and extracellular matrix proteins. The periostin gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Invasion and metastasis are the fundamental biological features of malignancies, leading to poor prognosis or even death in patients (Ye et al, 2017). In this study, miR‐93‐5p mimics and si‐PD‐L1 were discovered to weaken the migration and invasion of SW480 cells, but miR‐93‐5p inhibitor‐induced totally different effects.…”
Section: Discussionmentioning
confidence: 99%
“…Invasion and metastasis are the fundamental biological features of malignancies, leading to poor prognosis or even death in patients (Ye et al, 2017). In this study, miR‐93‐5p mimics and si‐PD‐L1 were discovered to weaken the migration and invasion of SW480 cells, but miR‐93‐5p inhibitor‐induced totally different effects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is logical to postulate that p53 and pRb play a vital role in RBBP6‐mediated PCa. Invasion and metastasis are the fundamental biological features of malignancies, leading to poor prognosis or even death in patients (Ye, Shen, Qiu, Li, & Wang, 2017). Yoshitake et al (2004) reported a significant upregulation of RBBP6 enhanced tumor cell proliferation in invasive esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We consistently noted increased expression of periostin in non-lesional bone at the edge of growing benign and malignant bone tumours. It has been shown that periostin plays a role in the progression of inflammatory and neoplastic lesions [ 6 , 11 , 12 , 23 ]. Periostin is known to be expressed by fibroblasts in RA, carcinomas and other malignant tumours [ 26 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been identified in rheumatoid arthritis (RA) and osteoarthritis (OA) joints [ 8 , 9 ] with a recent study identifying periostin as a key regulator in RA synoviocyte migration/invasion associated with pannus formation [ 10 ]. Periostin is also expressed in a number of cancers where it is thought, by various mechanisms, to play a role in tumour progression [ 3 , 6 , 11 , 12 ]. Periostin has been identified in a few bone tumours, including fibrous dysplasia and osteosarcoma [ 13 15 ], but its expression in other bone neoplasms has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%